The Quest for Molecular Regulation Underlying Unisexual Flower Development - Sobral, Rómulo; Silva, Helena G.; Morais-Cecílio, Leonor; Costa, Maria M. R. (Frontiers in Plant Science, 2016)
The understanding of the molecular mechanisms responsible for the making of a unisexual flower has been a long-standing quest in plant biology. Plants with male and female flowers can be divided mainly into two categories: dioecious and monoecious, and both sexual systems co-exist in nature in ca of 10% of the angiosperms. The establishment of male and female traits has been extensively described in a hermaphroditic flower and requires the interplay of networks, directly and indirectly related to the floral organ identity genes including hormonal regulators, transcription factors, microRNAs, and chromatin-modifying proteins. Recent transcriptomic studies have been uncovering the molecular processes underlying the establishment of unisexual flowers and there are many parallelisms between monoecious, dioecious and hermaphroditic individuals. Here, we review the paper entitled “Comparative transcriptomic analysis of male and female flowers of monoecious Quercus suber” published in 2014 in the Frontiers of Plant Science (volume 5 | Article 599) and discussed it in the context of recent studies with other dioecious and monoecious plants that utilized high-throughput platforms to obtain transcriptomic profiles of male and female unisexual flowers. In some unisexual flowers, the developmental programs that control organ initiation fail and male or female organs do not form, whereas in other species, organ initiation and development occur but they abort or arrest during different species-specific stages of differentiation. Therefore, a direct comparison of the pathways responsible for the establishment of unisexual flowers in different species are likely to reveal conserved modules of gene regulatory hubs involved in stamen or carpel development, as well as differences that reflect the different stages of development in which male and/or female organ arrest or loss-of-function occurs.